A Schematic Overview of the Current Status of Male Infertility Practice - Agarwal, Ashok (World J Mens Health, 2020)
The practice of male infertility has dramatically evolved over the past few decades. This has been achieved after the realization of the important contribution the male counterpart holds in the couple's infertility. It is also supported by a number of breakthroughs in the diagnosis and treatment of this medical condition. Several tests to investigate sperm quality and function were introduced along with refinements and/or institution of novel surgical techniques that can correct several causes of infertility. This manuscript is aimed at highlighting the current state of male infertility practice in a robust, schematic method addressing a broader audience involved in the treatment of male infertility.